On the role of the concept of noospheric knowledge in the era of technoscience - Chernikova Irina (EDP Sciences, 2021)
The article examines the changes that characterize modern science and scientific research, which have been embodied in the phenomenon of technoscience. Technological science is distinguished from traditional science by a new form of cognitive organization, integrating fundamental and applied research, natural science and human knowledge. It is both a theoretical activity for the production of ideas and social practice. It is substantiated that technoscience, which is both a theoretical construct and a social practice, embodies the project of noospheric knowledge, about which the outstanding Russian scientist V.I. Vernadsky wrote. His teaching expressed the idea of a new science, and by characterizing it, he stressed that science can’t be considered only as a collection of facts and limited to its instrumental functions, he understood it as the most powerful and important spiritual movement, contributing to the formation of the noosphere - the sphere of reason. Scientific knowledge, which is formed in the consequence of integrative tendencies in modern science, manifested in the systemic and holistic scientific worldview, in transdisciplinary studies, in the convergence of natural science and humanities knowledge, is designated as technoscience. It is shown that the noospheric science of V.I. Vernadsky, based on the wise mind, which he foresaw as the coming stage of the natural historical process, can be compared with the phenomenon of technoscience.